Design of RF filter based on RF components - Haris, Norshakila (2008)
Inductors, L, and capacitors, C, are among the most important circuit elements, especially for the radio frequency, RF, applications. Such applications of these components include frequency-tuning circuits, filters, mixers, and matching networks. This thesis presents the design and modelling of RF filters that consist of on-chip RF components. Firstly, two on-chip RF components have been separately designed before they were formed into an RF filter. The chosen configurations are the interdigital capacitor and spiral inductor. The effects of parameter variations on quality factor and inductance or capacitance values were investigated using simulation software. Upon achieving the desired performances, the components were arranged into series and shunt, forming two corresponding filter configurations. Both configurations were then connected to form a single stage series-shunt LC filter using parallel connection. Simulation results showed that both components operate well at the desired 13 GHz RF frequency of operation. The series and shunt LC filters demonstrate characteristics of a bandpass filter. At -3 dB or half-power insertion and return losses, both exhibit operating bandwidths from 8 GHz to 11 GHz, i.e. 3.0 GHz or 32 %. In ratio form, this is 11/8 = 1.375 which is quite broad. The single stage series-shunt LC filter also demonstrates characteristics of a bandpass filter. It exhibits slightly less -3 dB operating bandwidth from 8.75 GHz to 10.25 GHz, i.e. 1.5 GHz or 16 %. In ratio form, this is 10.25/8.75 = 1.17 which is slightly broad. This is halved that of the series and shunt LC filters. Hence, the former exhibits a maximum Q factor of approximately 3.2, which is doubled that of the single stage series-shunt LC filter.